PENGARUH OPINI AUDIT, PERTUMBUHANPERUSAHAAN, UKURAN KAP, DAN PERGANTIAN MANAJEMEN TERDAP VOLUNTARY AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR - Sofiana Sofiana; Nur Diana; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to analyze the factors that affect the voluntary transfer of auditorsat manufacturing companies listed on the Indonesia Stock Exchange (BEI). Thepopulation in this study is the financial statements of manufacturing companieslisted on the Indonesia Stock Exchange (BEI) in the period 2011-2016. Thenumber of manufacturing companies sampled in this research is 30 observationcompanies obtained by the method of purposive sampling. Data analysistechnique used is logistic regression analysis with SPSS. Based on the analysis,the result of the research shows that audit opinion variable, company growth,KAP size, and change of management have significant influence on companysample to perform voluntary auditor switching.Keywords: audit opinion, company growth, KAP size, change of management,voluntary auditing switching